ANALISIS UJI TARIK KOMPOSIT SERAT BATANG KELAKAI DENGAN VARIASI KATALIS UNTUK PEMBUATAN MATERIAL BUMPER MOBIL - Rusly, Muhammad; Sulistyowati, Rita; Lumban Toruan, Parmin (Prodi Fisika FST UNJA, 2023)
A research was conducted to create car bumper materials using natural kelakai plant fibers combined with a catalyst and resin as a binding agent in the composite. The main goal of the study was to examine the tensile strength of the kelakai fiber composite with different catalyst variations and assess the impact of these catalyst changes on the bumper material's tensile strength. The composite materials were prepared in three test specimens with catalyst compositions of 2,5%, 5%, and 7,5%, respectively, based on a 20 mL resin composition. These samples underwent tensile testing using a Universal Testing Machine (UTM). The results revealed that the tensile strength of the kelakai fiber composite increased with higher catalyst percentages. At 2,5%, 5%, and 7,5% catalyst compositions, the tensile strengths were measured as 0,37 N/mm2, 0,41 N/mm2, and 0,47 N/mm2, respectively. Additionally, the elongation values for the catalyst portion are 1,11%, 2,22%, and 3,89% and the Young's modulus values are 0,33 N/mm2, 0,18 N/mm2, and 0,12 N/mm2, respectively. The study demonstrates the significant influence of catalyst variations on the tensile strength of the kelakai fiber composite.